Análisis de la devolución del impuesto al valor agregado a los adultos mayores en el cantón Piñas provincia de El Oro, en el periodo 2021 - Bustamante Suárez, Xavier Andrés (2023)
The Constitution of the Republic of Ecuador recognizes the rights of priority groups, so that older adults as part of this sector have benefits, including tax benefits that allow them to access a better quality and lifestyle. The present degree work was developed with the objective of measuring the level of knowledge about the VAT refund in the acquisition of products for personal use and consumption in the elderly of the Piñas canton, province of El Oro, using an investigation of a quantitative approach, of descriptive, transversal and deductive design. As a data collection technique, a survey was applied to 23 older adults belonging to the Piñas canton, which have been selected using a non-probabilistic test for convenience. As a main result, it has been defined that there is a high level of ignorance in favor of the VAT refund for older adults, with 70 % of the sample analyzed, which allows us to conclude that the application of a training plan focused on the subject is necessary. VAT refund for older adults, established groups and their families if necessary, thus defining the specific proposal of this study. Keywords: IVA, SRI, refund, senior citizen,